Performance of food–feed maize and cowpea cultivars under monoculture and intercropping systems: Grain yield, fodder biomass, and nutritive value - Sanfo, Abroulaye; Zampaligré, Nouhoun; Kulo, Abalo E.; Somé, Sanyour; Traoré, Kadiatou; Rios, Esteban F.; Dubeux, José C. B.; Boote, Kenneth J.; Adesogan, Adegbola (Frontiers in Animal Science, 2023)
Livestock feeding in Burkina Faso is characterized by a recurrent deficit in both the quality and the quantity of fodder during the dry season, which affects animal performance. To overcome this, quality fodder/forage production is an alternative. Therefore, this study evaluated food- and feed-improved cultivars of maize and cowpea in intercropping trials using the “mother and baby trials” approach with crop–livestock farmers. The mother trial comprised a randomized block design with eight treatments and four replicates: two cowpea (KVx745-11P and Tiligré) and two maize cultivars (Barka and Espoir), and grown under two cropping systems (monoculture and intercropping). Baby trials were established on-farm and involved 30 farmers during two seasons (2019 and 2020) in four villages in the South Sudan zone of Burkina Faso. Data were collected on (1) weed density and biomass, (2) grain yield and fodder biomass, (3) intercropping efficiency, and (4) fodder nutritive value. Data were analyzed using ANOVA and the least significant difference (LSD) means separation at a 5% threshold. The results revealed that maize and cowpea intercropping significantly reduced weed biomass (p ≤ 0.05). In monoculture, the maize cultivar Barka produced a greater grain yield (4980 kg/ha) and fodder biomass [6259 kg dry matter (DM)/ha] than the cultivar Espoir, which produced a grain yield of 2581 kg/ha and fodder biomass of 4952 kg DM/ha. The cowpea cultivars, KVx745-11P and Tiligré, were similar (p ≥ 0.05) in terms of fodder biomass (2435–2820 kg DM/ha) and grain yield (1152–1163 kg/ha). For the intercropping system, land equivalent ratios for fodder biomass (1.18:1.41) and grain yield (1.02:1.44) were greater than 1; intercropping also had better productivity system indexes than the monoculture cropping system. The crude protein concentration of fodder was greater for Barka maize (9.5%–9.8%) than for Espoir maize (8.5%–8.7%). The crude protein concentration was greater for cowpea KVx745-11P (19%–21.8%) than for cowpea Tiligré (15%–17%). Intercropping both Barka maize and cowpea KVx745-11P was the most productive cropping system for maximizing grain and fodder production for crop–livestock farmers in the South Sudan zone of Burkina Faso.